PENANAMAN NILAI KEJUJURAN PADA ANAK DI LINGKUNGAN KELUARGA - Neneng Sunengsih (stit-islamic-village, 2022)
The purpose of this study is to find out how the role of parents in instilling the value of honesty in children in the family environment. As we know that there are many dishonest practices that are carried out in both small and large cases. Therefore, to make honest adults, it is necessary to nurture them from the age of children, especially in the family environment and as parents, they must be able to become the center of education for their children at home. This research is a qualitative field research where the research subjects are parents. The methods used in data collection are observation, interviews and documentation. The data analysis technique in this study used interactive data analysis techniques Miles & Huberman which included data collection, data reduction, data presentation and conclusion drawing. The data validity technique used in this study is the degree of confidence test in which there is a triangulation technique, in this case is source triangulation, namely re-checking the data obtained through different data sources. The results of the study show that in general the parents in Pingku Village have understood their role in the family, especially in instilling the value of honesty in children. In general, the implementation is quite good, but not perfect, this is due to several factors that affect parents, namely limited knowledge, environment, economic conditions, gender and so on.